Evaluating photodynamic therapy vs. subthreshold micropulse laser for central serous chorioretinopathy: a retrospective study = Vergleich von photodynamischer Therapie mit Subthreshold-Micropulse-Lasertherapie bei Chorioretinopathia centralis serosa - Spitznagel, Tahm; Fasler, Katrin; Zoellin, Jay; Gunzinger, Jeanne Martine; Sommer, Chiara; Kinzl, Stephan; Muth, Daniel Rudolf; Turgut, Ferhat; Saad, Amr; Becker, Matthias D.; Somfai, Gabor Mark; Zweifel, Sandrine (Klinische Monatsblätter für Augenheilkunde, 2025)
Background: Our study aims to compare the efficacy of half-dose photodynamic therapy with verteporfin (PDT) and subthreshold micropulse laser (SML) in patients with central serous chorioretinopathy (CSCR) with regards to subretinal fluid (SRF) resorption, visual acuity (VA), and central subfield thickness (CST). Patients and Methods: We conducted a retrospective multicentre clinical study at the Departments of Ophthalmology at the University Hospital Zurich and Stadtspital Zürich, Switzerland. The study included patients with acute and chronic CSCR who underwent PDT, SML, or both sequentially between June 1, 2020 and December 31, 2023. The primary outcome was the reduction in SRF at three and six months post-treatment. The secondary outcomes included change in CST VA at the same intervals. Results: A total of eighty-one eyes were analysed (33 PDT, 35 SML, thirteen combined). SRF reduction was statistically significant at both three and six months in the PDT (p < 0.001) and SML groups (p < 0.001). The combined treatment group showed a significant reduction in SRF only at six months (p = 0.001). At three months, PDT resulted in a significantly greater SRF reduction than the combined group. Conclusions: Both PDT and SML demonstrated improvements in SRF, CST and VA, with SML presenting as a comparable alternative, particularly in cases where access to verteporfin is limited.